Validation of an albumin-indocyanine green-based China liver cancer staging system to evaluating resectable hepatocellular carcinoma patients and comparison with the Child-Pugh-based China liver cancer staging system - Chen, MinQiang; Ren, Chao; Wang, MengXia; Yu, Min; Wu, Bo; Zhuang, Bo; Jin, JianXiang; Zhang, YaoQi; Yu, ShiAn (Frontiers in Oncology, 2025)
AimHere, the utility of an albumin-indocyanine green-based China liver cancer (CNLC) staging system (ALICE-CNLC) as a tool for the prognostic assessment of hepatocellular carcinoma (HCC) patients was evaluated, comparing this system to the Child-Pugh score-based CNLC staging system.MethodsThe cohort for this study included 331 patients with HCC who had undergone hepatectomy at Jinhua Municipal Central Hospital Medical Group in China from April 2012-June 2021 and had postoperative pathology-confirmed HCC. Kaplan-Meier survival curves were generated, with log-rank tests used to examine prognostic factors. Univariate and multivariate analyses were used for identification of outcome predictors using Cox proportional hazards regression.ResultsThe prediction of overall survival (OS) by the ALICE-CNLC system for patients with stage Ia disease was markedly better than that for patients with stage Ib and IIa disease (P=0.010, P=0.026), while the latter groups did not differ significantly (P=0.796). The ALICE-CNLC system predicted the 3-year recurrence-free survival (RFS) rates for patients with stage Ia, Ib, and IIa disease to be 50.4%, 47.7%, and 25%, respectively, with significant differences among the groups (P=0.033, P<0.001, and P=0.043). These results were similar to those of the CNLC staging system.The OS and RFS did not differ significantly between the same grades of patients evaluated with the ALICE-CNLC and CNLC staging systems.ConclusionThe ALICE-CNLC and CNLC staging systems did not show significant differences in predicting the prognosis of patients with HCC who have undergone hepatectomy.